2016
DOI: 10.18825/irem.77735
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Corporate Entrepreneurship Strategy for Competitive Advantage

Abstract: Current competitive environment is rapidly changing. In today's business environment, organizations are having an increasingly difficult time in creating competitive advantages. The main reason for this is the ease in contemporary business life for organizations to reach the same or very similar resources. Firms need innovation to create and sustain success and effectiveness. In such a highly competitive business life, the importance of creating competitive advantages for organizations based on unique resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…They are also given the opportunity to manage development funds from both the government and outside parties. The basic concept of empowerment referred to as alternative development that requires inclucive democracy, approprite economic growth, gender equality and intergeranational equality [19]. Chambers states that economic empowerment in society is a concept of economic and political development that encapsulates various social values [20].…”
Section: Iv4 Results Of Community Economic Empowerment In Business Gr...mentioning
confidence: 99%
“…They are also given the opportunity to manage development funds from both the government and outside parties. The basic concept of empowerment referred to as alternative development that requires inclucive democracy, approprite economic growth, gender equality and intergeranational equality [19]. Chambers states that economic empowerment in society is a concept of economic and political development that encapsulates various social values [20].…”
Section: Iv4 Results Of Community Economic Empowerment In Business Gr...mentioning
confidence: 99%
“…Several studies discovered that intrapreneurship contains achievement motivation (Collins et al, 2009;Dhewanto, 2013;Aarakit & Kimbugwe, 2015;Baruah & Ward, 2015;Mahmoud, Ahmad, & Poespowidjojo, 2018). Furthermore, achievement motivation was related to the work environment, reward system, management support, and job satisfaction (North, 2015;Enginoğlu & Arikan, 2016;Widya-Hastuti, Talib, Wong, & Mardani, 2016;McDowell, 2017;Falola et al, 2018). They are treated as the sub-focuses of this research.…”
Section: Intrapreneurship In Retail Businessmentioning
confidence: 96%
“…Therefore, CE is critical in today's environment as its benefits are remarkable for many businesses and organizations (including in the industry sector) and it has a significant effect on organizational performance (Behram and Özdemirci, 2014;Dess et al, 2003;Kassa and Raju, 2015). Previous studies have found that CE activities such as innovativeness, risktaking and corporate venturing are conducive to financial performance (Enginoglu and Arikan, 2016;Kuratko et al, 2015;Lumpkin and Dess, 1996). In recent years, organizations have been surrounded by a dynamic and turbulent environment with extremely competitive markets.…”
Section: Introductionmentioning
confidence: 99%